Causes, Effects of Stress and the Coping Mechanism of the Bachelor of Science in Information Technology Students in a Philippine University - Generoso N. Mazo (Intelektual Pustaka Media Utama, 2015)
The causes and levels of stress vary. The study of Information Technology is basically a rigorous one as it is designed to prepare students for the actual demands in the world of work. This study sought to determine the causes of stress, the effects of stress, and the stress coping mechanisms of Bachelor of Science in Information Technology students in the Leyte Normal University, Tacloban City. It tested some assumptions using the descriptive survey method with 51 respondents. Thesis writing/research and school requirements/projects were the most common causes of stress. Sleepless nights and irritable/moody feeling were the common effects of stress. There was disparity on the causes and effects of stress between the male and female respondents. The use of computer and praying to God were the common stress coping mechanisms. There was an observed disparity between the male and female responses.